2019
DOI: 10.1080/21691401.2019.1626405
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: GPR39 agonist TC-G 1008 ameliorates IL-1β-induced chondrocyte senescence

Abstract: Aging-related osteoarthritis (OA) is the most common type of arthritis. Chondrocyte senescence has been linked with the pathogenesis of OA. Here, we examined the expression of GPR39 in chondrocytes and its modulatory effect on IL-1b-induced cellular senescence. We show that GPR39 is moderately expressed in human chondrocytes and its expression is repressed by the pro-inflammatory cytokine IL-1b. The GPR39 agonist TC-G 1008 mitigates IL-1b-induced chondrocyte senescence. Mechanistically, we show that TC-G 1008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Based on the existing reports, TP53, also known as p53, contributes to transcriptional regulation of the cell cycle, DNA repair, cell survival, and cell metabolism [35]. Inhibition of p53 exerts a substantial effect on promoting the senescence of IL-1β-induced chondrocytes [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the existing reports, TP53, also known as p53, contributes to transcriptional regulation of the cell cycle, DNA repair, cell survival, and cell metabolism [35]. Inhibition of p53 exerts a substantial effect on promoting the senescence of IL-1β-induced chondrocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existing reports, TP53, also known as p53, contributes to transcriptional regulation of the cell cycle, DNA repair, cell survival, and cell metabolism [ 35 ]. Inhibition of p53 exerts a substantial effect on promoting the senescence of IL-1 β -induced chondrocytes [ 36 ]. The potential role of TP53 in the regulation of inflammation has been described, whereby it significantly inhibits the production of proinflammatory factor IL-6 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a speci c agonist of GPR39, TC-G 1008 is widely used to explore the effect of GPR39 activation [25,43,44]. Previous studies have shown that treatment with TC-G 1008 (100 nM and 1 μM) enhanced keratinocyte proliferation through an ERK-dependent pathway [45].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that activation of SIRT1 is a neuroprotective agent for ischemic stroke through several mechanisms [55][56][57][58]. TC-G 1008 treatment mitigated IL-1b-induced inhibition of SIRT1, and the effect of TC-G 1008 on p53 acetylation and chondrocyte senescence were abrogated when SIRT1 was silenced [44]. Previous studies have indicated that PGC-1α was a major regulator of ROS metabolism and mitochondria biogenesis which closely related to the pathology of ischemic diseases and neurodegenerative diseases [59].…”
Section: Discussionmentioning
confidence: 99%